2008
DOI: 10.1021/es802182f
|View full text |Cite
|
Sign up to set email alerts
|

Is Lipid Peroxidation Induced by the Aqueous Suspension of Fullerene C60 Nanoparticles in the Brains of Cyprinus carpio?

Abstract: This study aimed to clarify whether fullerene C60 nanoparticles induced lipid peroxidation in Cyprinus carpio brains. A stable well-characterized aqueous suspension of C60 nanoparticle (diameter: 50th and 95th percentiles, 36 and 95 nm respectively) with 0.1% Tween80 solution was prepared by bead milling. Lipid hydroperoxides (LPO) were measured in vitro in homogenized fish brain tissues containing 33 microg/mg-protein dispersed C60 nanoparticles under light and dark conditions to verify the lipid peroxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 19 publications
2
43
0
Order By: Relevance
“…Later in vivo toxicity study of C60 using fathead fish and medaka by Oberdorster et al [9] failed to prove protein or DNA damage or cellular oxidation responses. Shinohara et al [10] reported that C60 exposure did not induce any lipid peroxidation of the brain tissue of C. carpio in vivo. Henry et al [11] concluded that trace solvent residues such as tetrahydrofuran, used in the preparation of C60 fine suspensions, and its degradation products were neuro-toxicants that could be responsible for damaging the brain of largemouth bass.…”
Section: Introductionmentioning
confidence: 98%
“…Later in vivo toxicity study of C60 using fathead fish and medaka by Oberdorster et al [9] failed to prove protein or DNA damage or cellular oxidation responses. Shinohara et al [10] reported that C60 exposure did not induce any lipid peroxidation of the brain tissue of C. carpio in vivo. Henry et al [11] concluded that trace solvent residues such as tetrahydrofuran, used in the preparation of C60 fine suspensions, and its degradation products were neuro-toxicants that could be responsible for damaging the brain of largemouth bass.…”
Section: Introductionmentioning
confidence: 98%
“…Although the toxic effects of C 60 are still mostly unknown, especially those related to neurotoxicity, some general aspects have already been addressed. For instance, C 60 is reported to be cytotoxic to various mammalian cells [8] and it has been shown to induce lipid peroxidation in human cells [9], in brain of juvenile largemouth bass ( Micropterus salmoides ) [10], and in common carp ( Cyprinus carpio ) [11]. Moreover, C 60 was classified as “very toxic” to aquatic organisms by the grid for the potential ecotoxicological hazard evaluation which is based mainly on toxicity to fish, Daphnia , and algae and in data about degradability of the substance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Petersen et al (2009) reported that carbon nanotubes accumulated in the gut of D. magna and were not absorbed into cellular tissues, but the addition of algae resulted in significant depuration in the first few hours. Shinohara et al (2009) demonstrated that buckminsterfullerene (C 60 ) in Cyprinus carpio induced lipid peroxidation under light, but did not reach the brain. Some nanoparticles cause gill injury (Griffitt et al, 2007) and are lethal (Griffitt et al, 2008) to fish or fish embryos.…”
Section: Introductionmentioning
confidence: 99%